Penerapan Metode Proyek Dalam Kurikulum Merdeka Pada Mata Pelajaran Al-Quran Hadits - Miftahul Jannah; Jumari Jumari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This study examines the application of the project method in learning Al-Quran Hadith class X at MAN 4 Jombang in the context of the Merdeka Curriculum. Using a qualitative approach with observation, interview, and documentation analysis methods, this study aims to understand the implementation, impact, and challenges of applying the project method. The results show that the implementation of the project method has brought significant changes in the learning process, creating a more interactive and learner-centered learning environment. The main characteristics of learning include independent completion of tasks, full responsibility of learners, and involvement of various parties. Positive impacts are seen in increased motivation, understanding of the material, and development of 21st-century skills. However, challenges such as time constraints, variations in learners‘ abilities, and educators’ professional development needs are still faced. This research provides insights into the potential integration of contemporary learning approaches in Islamic education and highlights the importance of systemic support in the implementation of educational innovations. The findings can serve as a reference for the development of educational policies and practices that are responsive to the needs of learners in the modern era while maintaining the core values of Islamic education.